Research on Urban Road Network Evaluation Based on Fractal Analysis - Wen Wen; Wenhui Zhang; Hongxing Deng (Journal of Advanced Transportation, 2023)
The structure of the urban road network affects the mode of urban development and the position of urban social and economic activities, families, and employment centers. Therefore, it is necessary to consider the supply inequality of urban road network and its impact on urban development so as to form a sustainable and fair urban development model in cities. Based on the fractal analysis, this paper seeks the evaluation index of urban road network layout and internal structure characteristics to guide the optimization and adjustment of the urban road network, which is of great significance for guiding urban land use, effectively utilizing geospatial space, and promoting sustainable urban development, and attempts to apply the fractal analysis concept to evaluate the urban road network in Harbin, China. It is found that there is a good relationship between the length of the urban road network and the build-up area. Therefore, fractal analysis is used to reasonably determine the spatial demand of incremental road networks, considering the impact of road network increase on development mode. This paper argues that fractal analysis is an auspicious tool for the evaluation of urban road networks, including solving the problem of supply inequality in urban road networks, which is very suitable for the gradual construction of road networks in urban situations, especially in the development environment of road networks with scarce resources.